Pengaruh Variabel Makroekonomi dan Indikator Rasio Keuangan Terhadap Profitabilitas Bank Umum Konvensional di Indonesia - Yola, Elvi; Satrianto, Alpon (Universitas Negeri Padang, 2024)
Banks are part of the financial system which plays an important role in a countrys economic development. This research will examine the influence of economic growth, inflation, Non Performing Loan (NPL), Net Interest Margin (NIM), and Operating Cost of Operating Income (BOPO) on Profitability as measured by Return on Asset (ROA). This study uses quarterly time series data from 2005-2022. This results of this study indicate that the macroeconomic variables, namely economic growth, have a negative and significant effect on profitability, and inflation has no significant effect on profitability. While the financial ratio indicator NPL has a negetive and significant effect on profitability, while NIM has a positive and significant effect on profitability, and BOPO has a negetive ang significant effect on profitability. The effect of these variable on profitability is expected to encourage an upward trend in profitability.